Efficacy of Pediococcus acidilactici PA53 in preventing high-fat diet-induced non-alcoholic fatty liver disease in mice - Niu, Yue; Liu, Peng; Chen, Yu; Yao, Yichen; Bu, Shurui (Frontiers in Immunology, 2026)
AimTo investigate the therapeutic and preventive effects of the probiotic Pediococcus acidilactici PA53 on high-fat diet (HFD)-induced non-alcoholic fatty liver disease (NAFLD) in mice, and to evaluate its efficacy compared to curcumin (a well-recognized anti-NAFLD agent), thereby advancing the mechanistic and practical understanding of probiotic-based interventions for metabolic liver diseases.MethodsThe experiment comprised five groups: Control group, Model group, PA53 prevention group, PA53 treatment group, and curcumin group. NAFLD was induced by feeding mice a high-fat diet (HFD), with body weight recorded weekly. At the end of the experiment, serum, liver, and ileum samples were collected from the mice. The levels of serum inflammatory factors, including tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), and interferon-inducible protein-10 (IP-10), as well as related blood biochemical markers such as alanine aminotransferase (ALT), glucose (GLU), triglyceride (TG), cholesterol (CHO), and low-density lipoprotein cholesterol (LDL-C), were measured. Hepatic lipid deposition was evaluated using hematoxylin and eosin (H&E) staining and oil red O staining. Additionally, fecal samples were collected at multiple time points and subjected to 16sRNA sequencing to assess changes in the gut microbiota.ResultsPA53 significantly attenuated body weight gain, liver lipid accumulation, serum inflammatory cytokine levels while normalizing gut microbiota composition in mice, bringing these parameters closer to those of the control group. Compared to curcumin, PA53 proved more effective in controlling body weight gain and reducing liver fat accumulation. Furthermore, the preventive regimen yielded better outcomes than the therapeutic effect. While PA53 was less effective than curcumin in modulating certain immune responses and reducing specific cytokines (such as IL-6, IL-1β, TNF-α and IP-10), it still exerted significant anti-inflammation effects.ConclusionIn conclusion, PA53 demonstrates potential efficacy in mitigating HFD-induced NAFLD in mice, with its preventive effect appearing comparatively more prominent. Notably, PA53 exhibited superior performance over curcumin in key metabolic endpoints, which furnishes novel empirical evidence for its putative role in NAFLD management and augments the current body of knowledge regarding probiotic-based therapeutic strategies for metabolic liver diseases.